2009
DOI: 10.3390/molecules14103868
|View full text |Cite
|
Sign up to set email alerts
|

Fu et al. A New Sesquiterpene from the Fruits of Daucus carota L. Molecules 2009, 14, 2862-2867

Abstract: We realized that the affiliations of the authors were incorrectly listed in our paper published in Molecules recently [1]. [...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 1 publication
(1 reference statement)
2
85
0
Order By: Relevance
“…Pierpaoli et al 2003, for a review). The dominant discrepancy between cosmic shear and X-ray clusters has recently been reduced by Jarvis et al (2006), who measured σ 8 ≈ 0.81 for m = 0.26 when using cosmic shear alone, followed by Benjamin et al (2007), who used the improved galaxy photometric redshifts of Ilbert et al (2006), and measured σ 8 = 0.84 for m = 0.24 and Fu et al (2008), who found a consistent value. To clarify these discrepancies, one needs to measure both the power-spectrum and the M-T relation normalizations σ 8 and M * , as we discuss here.…”
Section: Discussionmentioning
confidence: 99%
“…Pierpaoli et al 2003, for a review). The dominant discrepancy between cosmic shear and X-ray clusters has recently been reduced by Jarvis et al (2006), who measured σ 8 ≈ 0.81 for m = 0.26 when using cosmic shear alone, followed by Benjamin et al (2007), who used the improved galaxy photometric redshifts of Ilbert et al (2006), and measured σ 8 = 0.84 for m = 0.24 and Fu et al (2008), who found a consistent value. To clarify these discrepancies, one needs to measure both the power-spectrum and the M-T relation normalizations σ 8 and M * , as we discuss here.…”
Section: Discussionmentioning
confidence: 99%
“…This is what the approach which is usually adopted such as in [7] for the CFHTLenS survey and in [8] for the DES survey. There exist however alternative approaches that give complementary information.…”
Section: Introductionmentioning
confidence: 90%
“…Gravitational lensing information and the integrated Sachs-Wolfe effect of the cosmic microwave background act to constrain G light . We have seen that current data are weak in the ability to test G matter , with uncertainties of order one, while G light can be determined to roughly 10% from the Canada-France-Hawaii Telescope Legacy Survey lensing data [10] and the WMAP CMB temperature power spectrum [11]. However, note that this precision does not indicate accuracy; the deviation from GR seen in the bottom right panel, for example, arises from acknowledged observational systematics [8].…”
Section: The Differences Of Gravitymentioning
confidence: 99%
“…Constraints are shown on the 8 parameters of post-GR model independent gravity, from current and simulated future data. Dotted contours show the 68% and 95% confidence regions from current WMAP CMB [11], CFHTLS lensing [10], and Union2.1 supernova distance data [12], while solid black contours show constraints from simulated data of the next generation BigBOSS galaxy redshift survey (marginalized over galaxy bias) plus Stage III experiments. Small red contours include as well a highly optimistic galaxy weak lensing survey covering 4000 deg 2 with a galaxy number density of 55 arcmin −2 .…”
Section: The Paths Of Gravitymentioning
confidence: 99%